An international clinical study of ability and disability in ADHD using the WHO-ICF framework - Mahdi, S.; Ronzano, N.; Knüppel, A.; Dias, J.; Albdah, A.; Chien-Ho, L.; Almodayfer, O.; Bluschke, A.; Karande, S.; Huang, H.; Christiansen, H.; Granlund, M.; et al. (Springer Medizin, 2018)
This is the fourth and final study designed to develop International Classification of Functioning, Disability and Health (ICF, and children and youth version, ICF-CY) core sets for attention-deficit hyperactivity disorder (ADHD). To investigate aspects of functioning and environment of individuals with ADHD as documented by the ICF-CY in clinical practice settings. An international cross-sectional multi-centre study was applied, involving nine units from eight countries: Denmark, Germany, India, Italy, Portugal, Saudi Arabia, Sweden and Taiwan. Clinicians and clinical researchers rated the functioning level of 112 children, adolescents and adults with ADHD using the extended ICF-CY checklist version 2.1a. The ratings were based on a variety of information sources, such as medical records, medical history, clinical observations, clinical questionnaires, psychometric tests and structured interviews with participants and family members. In total, 113 ICF-CY categories were identified, of which 50 were related to the activities and participation, 33 to environmental factors and 30 to body functions. The clinical study also yielded strengths related to ADHD, which included temperament and personality functions and recreation and leisure. The study findings endorse the complex nature of ADHD, as evidenced by the many functional and contextual domains impacted in ADHD. ICF-CY based tools can serve as foundation for capturing various functional profiles and environmental facilitators and barriers. The international nature of the ICF-CY makes it possible to develop user-friendly tools that can be applied globally and in multiple settings, ranging from clinical services and policy-making to education and research.